2018
DOI: 10.1016/j.artd.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapists collect different outcome measures after total joint arthroplasty as compared to most orthopaedic surgeons: a New England study

Abstract: BackgroundFollowing total knee and hip arthroplasty, patient progress can be assessed with patient-reported outcome measures (PROMs) and performance-based outcome measures (PBOMs). The American Joint Replacement Registry 2016 guide recommends collecting several measures, including Patient Reported Outcome Measure Information System Global, Knee Injury and Osteoarthritis Outcome Score Jr, and Hip Injury and Osteoarthritis Outcome Score Jr. This study aimed to assess the current and anticipated use of PROMs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…However, physiotherapists use different types of measurement instruments compared with orthopaedic surgeons. 18 To harmonise TJR clinical trial outcomes, it is important that all stakeholders agree on the core domain areas and on the instruments used to measure these areas. However, no information about such agreement is yet available in Germany.…”
Section: Open Accessmentioning
confidence: 99%
“…However, physiotherapists use different types of measurement instruments compared with orthopaedic surgeons. 18 To harmonise TJR clinical trial outcomes, it is important that all stakeholders agree on the core domain areas and on the instruments used to measure these areas. However, no information about such agreement is yet available in Germany.…”
Section: Open Accessmentioning
confidence: 99%
“…For example, one study recently found that physical therapists collect different outcome measures after total joint arthroplasty compared to most orthopaedic surgeons. 24…”
Section: Not All Proms Are Equalmentioning
confidence: 99%
“…As the number of TKA cases rise, there are greater pressures on surgeons and health-care systems to demonstrate that the benefits outweigh the associated costs [4] . Recovery of physical function is an important outcome of TKA and may be measured using patient-reported outcomes or performance-based outcomes [5] , [6] . Both are used to evaluate outcomes after TKA; however, orthopedic surgeons who use outcome measures tend to rely primarily on patient-reported outcomes which may not fully characterize the patient's physical function due to influences such as level of pain [5] , [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of physical function is an important outcome of TKA and may be measured using patient-reported outcomes or performance-based outcomes [5] , [6] . Both are used to evaluate outcomes after TKA; however, orthopedic surgeons who use outcome measures tend to rely primarily on patient-reported outcomes which may not fully characterize the patient's physical function due to influences such as level of pain [5] , [7] . There is a lack of widespread collection and use of patient-reported outcomes by orthopedic surgeons due to real and perceived barriers [8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation